Impact of Indoor Air Pollution on Health Outcomes in Pakistan: A Case Study of Multan District - Ishfaq, Mubasher; Gill, Abid Rashid (Pakistan Journal of Humanities and Social Sciences, 2023)
The current study intends to investigate the impact of indoor air pollution on health outcomes in Pakistan using data from 400 households in the Multan district. In order to find the presence of Indoor air pollution, readings of PM2.5 is used. The ordinary least square (OLS) method is used for data analysis. The study finds that indoor air pollution has a significant impact on physical and behavioral health symptoms. The study also finds that household head age, household size, household income, environmental concern, and the use of air cleaning device are the significant factors of physical health symptoms, while the variables household head age, education, household income, environmental concern, and environmental awareness are the significant factors of behavioral health symptoms. It is concluded that indoor air quality is essential in influencing the health status of the households. This study suggests that attempts should be made to improve indoor air quality by improving the housing structure and the socioeconomic status of the households.